Synthesis and Characterization of 2,4-Dichlorophenoxypropanoic Acid (2,4-DP) Herbicide Interleaved into Calcium-Aluminium Layered Double Hydroxide and the Study of Controlled Release Formulation - Farah Liyana Bohari; Nur Aishah Mohd Noor; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali; Nur Nadia Dzulkifli; Is Fatimah; Nurain Adam (Universitas Gadjah Mada, 2022)
The commonly used herbicide in agriculture, namely 2,4-dichlorophenoxypropanoic acid (2,4-DP), is an anionic herbicide used to interleave into the interlayer of calcium-aluminum layered double hydroxide (Ca-Al LDH) employing co-precipitation method to form a new nanohybrid labeled as CAL-2,4DP. The LDH compound serves as a host in supporting the herbicide’s controlled release formulation. The effective interleave was investigated by employing a powder X-Ray Diffraction (XRD) pattern at 0.025 M nanocomposite, which revealed that the basal spacing has increased from 8.0 Å to 23.8 Å. The ATR-FTIR spectra further supported the interleaving, where the nitrate peak (NO−) diminished, and the carboxylate ion (COO−) band appeared at 1653 cm−1. The percentage loading of CAL-2,4DP was 71.26%, calculated from the carbon content in the sample. The BET analysis shows that CAL-2,4DP was a mesoporous material relying on nitrogen-desorption isotherms. The release of 2,4-DP ions into the aqueous solutions followed the order of PO43− > CO32− > Cl− with a percentage of 83, 65, and 30%, respectively. This work indicates the successful interleaving process of the 2,4-DP anion and the potential of CAL-2,4DP as an eco-friendly agrochemical that can be beneficial for farmers in minimizing herbicide usage to the environment.